2022
DOI: 10.3389/fped.2022.909118
|View full text |Cite
|
Sign up to set email alerts
|

Value of Literature Review to Inform Development and Use of Biologics in Juvenile Idiopathic Arthritis

Abstract: BackgroundJuvenile idiopathic arthritis (JIA) is one of the most common pediatric inflammatory rheumatic diseases (PiRDs). Uncontrolled disease activity is associated with decreased quality of life and chronic morbidity. Biologic disease-modifying antirheumatic drugs (bDMARDs) and Janus kinase inhibitors (JAKi) have considerably improved clinical outcomes. For optimized patient care, understanding the efficacy-safety profile of biologics in subgroups of JIA is crucial. This systematic review based on published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Previous studies have shown a pattern of progression in TMJ deformities over time 30 . This difference can probably be explained by the fact that the children in the current study to a large extent received highly effective medication (bDMARDS) 31 , implicating low disease activity. Further, there are other possible explanations for TMJ deformities in children than JIA involvement.…”
Section: Discussionmentioning
confidence: 82%
“…Previous studies have shown a pattern of progression in TMJ deformities over time 30 . This difference can probably be explained by the fact that the children in the current study to a large extent received highly effective medication (bDMARDS) 31 , implicating low disease activity. Further, there are other possible explanations for TMJ deformities in children than JIA involvement.…”
Section: Discussionmentioning
confidence: 82%
“…The introduction of bDMARDs has markedly improved the efficacy of JIA treatment. 30 , 33 In addition, more patients can now avoid the safety concerns associated with conventional methotrexate and glucocorticoids, but there are still many issues to be examined regarding the short- and long-term safety of bDMARDs, including the risk of infection and potential risk of malignancy associated with their immunosuppressive effects. Future studies are needed to clarify these issues.…”
Section: Discussionmentioning
confidence: 99%
“…An enhanced understanding of the efficacy-safety balance of existing and new biologics will facilitate decision-making in clinical practice as well as the development of new treatment options in children with psoriasis. Exploratory meta-analyses and model-based meta-analysis can utilize integrated data from clinical controlled studies strengthening the knowledge of a particular drug and its efficacy and safety relative to other treatment options in adults and children (78,79). Metaanalysis, especially model-based meta-analysis, facilitates the bridging of clinical outcomes data from adult and pediatric patients and can be a useful quantitative tool for enhancing key decisions such as dose selection and study design (Pediatric Investigation Plan, PIP), product positioning, and go/no-go decisions in pediatric drug development (80)(81)(82).…”
Section: Use and Development Of Biologics In Pediatric Psoriasismentioning
confidence: 99%